War and relatedness - Enrico Spolaore; Romain Wacziarg (Center for Economic Studies and ifo Institute (CESifo), 2009)
We develop a theory of interstate conflict in which the degree of genealogical relatedness between populations has a positive effect on their conflict propensities because more closely related populations, on average, tend to interact more and develop more disputes over sets of common issues. We examine the empirical relationship between the occurrence of interstate conflicts and the degree of relatedness between countries, showing that populations that are genetically closer are more prone to go to war with each other, even after controlling for a wide set of measures of geographic distance and other factors that affect conflict, including measures of trade and democracy.
Keywords: D74; F51; F59; H56; 330; conflict; genetic distance; common issues; rival issues; Politischer Konflikt; Krieg; Soziale Beziehungen; Mensch; Spieltheorie; Theorie; Welt